An Analysis Of The Stunting Prevention Program At The Batang Quiz Village Health Center Deli Serdang District In 2022 - Asri Widiya Sitompul; Ermi Girsang; Ali Napiah Nasution (Jurnal Scientia, 2024)
Stunting is a linear growth disorder in children due to a chronic lack of nutritional intake. The consequences of malnutrition in children will have a major impact on future generations. The prevalence of stunting in Indonesia is 30.8%. This means that three out of ten children under the age of five experience growth disorders which will result in delays in thinking abilities and reduced levels of intelligence. Based on the map of the distribution of stunting in Deli Regency, it shows that there has been a decrease in the percentage of stunted toddlers in Deli Serdang Regency from 6.70% in 2019 to 2.64% in 2020. This shows that the convergence of programs/interventions in efforts to accelerate stunting prevention has been able to reduce percentage of stunted toddlers in Deli Serdang Regency. The research used in this research is quantitative research. The sample taken was 315 people using purposive sampling technique. The independent variables in the research are behavior, level of education, social status, p erceived benefits and perceived barriers to action. The dependent variable in this research is efforts to prevent stunting. In this study, it was found that 74.51% had a level of stunting prevention behavior. Stunting prevention in children aged 2 -5 years is influenced by behavior, while education level, social status, perceived benefits and barriers to action influence stunting prevention in children aged 2 -5 years.